Report on the planning implementation and evaluation of a health education project for the prevention of diarrhea among pre school children - Abayasiri, N.K (My University, 1996)
A report on the planning implementation and evaluation of a health education project for the prevention of diarrhea among pre school children in the DDHS area of Mirigama. Discusses the criterion employed to identify the problem, behavioral elements of the problem, identification of target groups, resources and the action plan for the proposed educational activity